دور سلوكيات فن الإتيكيت في شخصية مستهلك الخدمة الفندقية: دراسة نظرية تحليلية - المشهداني، خليل إبراهيم; تكلان، إبتهال خاجيك (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2016)
Proceeding from the importance of the subject of the behaviors of the art of etiquette and their potential impact on the personal consumer service hotel, and continue to increase the enrichment intellectual of these topics this study is an t to contain the problem of the study, which are summarized in the survival of these vital topics without the assurance of the process of linking the current has in this study and their contribution events in the accumulation of knowledge will miss the opportunity to hotel establishments to benefit them, and according to these debates and dilemmas of intellectual and practical problem of the study were formulated a set of themes that revolve around the role of the knowledge of the art of etiquette behaviors in personal consumer service hotel.
انطلاقا من أهمية موضوع سلوكيات فن الأتيكيت وتأثيراتها المحتملة على شخصية مستهلك الخدمة الفندقية، وتواصلا في زيادة الإثراء الفكري من هذه المواضيع جاءت هذه الدراسة في محاولة لاحتواء مشكلة الدراسة التي تتلخص في أن بقاء هذه المواضيع الحيوية دون توكيد لعملية الربط الحالية التي تمت في هذه الدراسة ومساهمتها في إحداث التراكم المعرفي سيفوت الفرصة على مؤسسات الفندقية للإفادة منها، وعلى وفق هذه التجاذبات والإشكاليات الفكرية والعملية جرت صياغة مشكلة الدراسة بمجموعة من المحاور التي تدور حول معرفة دور سلوكيات فن الأتيكيت في شخصية مستهلك الخدمة الفندقية.
Keywords: فن الاتيكيت -- سلوكيات فن الاتيكيت -- الخدمة الفندقية -- مستهلك الخدمة الفندقية